Towards people-centred approaches for effective disaster risk management: Balancing rhetoric with reality. (June 2015) - Scolobig, Anna; Prior, Tim; Schröter, Dagmar; Jörin, Jonas; Patt, Anthony
Abstract: Over the past two decades, decision-making in disaster risk management (DRM) has evolved significantly. This has resulted in a re-focus from a predominantly top-down, 'command and control' style of management, to the encouragement of 'people-centred' approaches and local participation. In this paper we critically explore this transition, particularly examining the teething problems related to the adoption of people-centred approaches, and especially to the transfer of DRM responsibility from the agencies in charge to the private citizens. We review traditional top-down approaches against a backdrop of changing circumstances relevant to disaster risk, and present some background to the international push for people-centred approaches, comparing the key characteristics of the two approaches. Using three case studies, we discuss how the personal responsibilities of citizens are weighed against the responsibilities of local authorities. The examples reveal a complex landscape characterised by insufficient resources at the local level, and lack of willingness among public at risk to share responsibility for disaster risk management with authorities. Moreover, local participation can create situations of conflict between public and private interests. If official authorities are to implement the new people-centred approach, they must better understand residents' perspectives and responsibility expectations, become more competent communicators, and be willing to engage in long-term dialogue with communities. This requires the courage to question existing institutional arrangements, and not only devolve power in DRM, but also relinquish responsibility to citizens. Future research must focus particularly on better understanding the benefits and challenges of shared state and civil responsibility in DRM theory and practice.